2017
DOI: 10.1515/hukin-2017-0110
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Control During the Bench Press Movement in an Elite Disabled and Able-Bodied Athlete

Abstract: The disabled population varies significantly in regard to physical fitness, what is conditioned by the damage to the locomotor system. Recently there has been an increased emphasis on the role of competitive sport in enhancing health and the quality of life of individuals with disability. One of the sport disciplines of Paralympics is the flat bench press. The bench press is one of the most popular resistance exercises used for the upper body in healthy individuals. It is used not only by powerlifters, but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 26 publications
1
22
0
1
Order By: Relevance
“…This result may be related to increased muscle activity of the prime-movers during the bench press (pectoralis major, anterior deltoid, triceps brachii) performed with the raised legs compared to the legs supported on the floor, as indicated by previous studies [ 27 ]. This finding was also shown by Golas et al [ 21 ], who found increased involvement of upper body muscles during bench press in an athlete with lower limb disability (limited kinesthetic sense and proprioception). It seems that in such situations the compensation of deficits occurs through the greater activity of the upper body muscles due to the lack of support for the legs.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This result may be related to increased muscle activity of the prime-movers during the bench press (pectoralis major, anterior deltoid, triceps brachii) performed with the raised legs compared to the legs supported on the floor, as indicated by previous studies [ 27 ]. This finding was also shown by Golas et al [ 21 ], who found increased involvement of upper body muscles during bench press in an athlete with lower limb disability (limited kinesthetic sense and proprioception). It seems that in such situations the compensation of deficits occurs through the greater activity of the upper body muscles due to the lack of support for the legs.…”
Section: Discussionsupporting
confidence: 83%
“…There are a large number of studies that evaluate the effectiveness of various conditioning activities on the upper-body PAPE effect [ 5 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] in groups of able-bodied athletes, but there is no replication of their protocols on disabled athletes. It seems that there is no reason to believe that this phenomenon may differ between able-bodied and disabled athletes; however, in case of the bench press performed with maximum effort, the position on the bench may have an impact on training outcomes [ 21 ]. During the bench press exercise or the BP throw, the athlete has four points of support: head, shoulders and upper back, buttocks, and feet.…”
Section: Introductionmentioning
confidence: 99%
“…Among the strength sports, the Paralympic Powerlifting (PP) has been gaining more and more followers, and the sport aims to lift the greatest possible load in the adapted bench press [16,17,18]. However, the studies have focused more on aspects of health, classification and etiology of injuries [12,19,20]. On the other hand, few studies have addressed aspects related to performance [18,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Esta importancia del PB radica en la alta solicitación de los grupos musculares intervinientes en la cintura 2021, Retos, 39, 459-464 © Copyright: Federación Española de Asociaciones de Docentes de Educación Física (FEADEF) ISSN: Edición impresa: 1579-1726. Edición Web: 1988-2041 escapular (Stastny et al, 2017), requiriendo principalmente de la musculatura del pectoral y del tríceps, y secundariamente de la porción anterior del deltoides y del serrato (Go³aoe et al, 2017;Saeterbakken et al, 2017). Además, estos músculos forman parte esencial en numerosos deportes que requieran elevados niveles de fuerza de los miembros superiores, como por ejemplo el powerlifting (Bengtsson, Berglund, & Aasa, 2018;Helms et al, 2017;Tillaar, 2019;van den Tillaar & Ettema, 2010).…”
Section: Introductionunclassified